Station 3A lymph node dissection does not improve long‐term survival in right‐side operable non‐small‐cell lung cancer patients: A propensity score matching study - Mu‐Zi Yang; Zi‐Hui Tan; Ji‐Bin Li; Hao Long; Jian‐Hua Fu; Lan‐Jun Zhang; Peng Lin; Xue Hou; Hao‐Xian Yang (Thoracic Cancer, 2022)
Abstract Background To investigate the impact of station 3A lymph node dissection (LND) on overall survival (OS) and disease‐free survival (DFS) in completely resected right‐side non‐small‐cell lung cancer (NSCLC) patients. Methods A total of 1661 cases with completely resected right‐side NSCLC were included. Propensity score matching (PSM) was performed to minimize selection bias, and a logistic regression model was conducted to investigate the risk factors associated with station 3A lymph node metastasis (LNM). The Kaplan–Meier method and Cox proportional hazards model were used to evaluate the impact of station 3A LND on survival. Results For the entire cohort, 503 patients (30.3%) underwent station 3A LND. Of those, 11.3% (57/503) presented station 3A LNM. Univariate and multivariate logistic analyses showed that station 10 LNM, tumor location, and the number of resected lymph nodes were independent risk factors associated with station 3A LNM. Before PSM, patients with station 3A LND had worse 5‐year OS (p = 0.002) and DFS (p = 0.011), and more drainage on postoperative day 1 (p = 0.041) than those without. After PSM, however, station 3A LND was not associated with the 5‐year OS (65.7% vs. 63.6%, p = 0.432) or DFS (57.4% vs. 56.0%, p = 0.437). The multivariate analysis further confirmed that station 3A LND was not a prognostic factor (OS, p = 0.361; DFS, p = 0.447). Conclusions Station 3A LND could not improve long‐term outcomes and it was unnecessary to dissect station 3A lymph nodes during surgery of right‐side NSCLC.